Immersing Android-based Teaching Module in Reading Class for Second Semester Students - Fakhrurriana, Ria (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
To comprehend the meaning in a sentence or passage, students need to practice and elevate their reading skill. Furthermore, some learning sources are made to facilitate students in improving their reading level. One of those is android-based module that was made by one of English lecturer in IAIN Kediri. After the product was published, this study aimed to implement it in reading class for second semester students. This study was conducted qualitatively by observing reading class where the android-based module is implemented. Additionally, this study provides students' response to the implementation of android-based module as well. Reading comprehension test was arranged to know whether or not the android-based module affect student's reading comprehension skill. In the end, this study indicates that android-based module helps the teacher to teach reading comprehension simply and facilitates students to elevate their reading comprehension skill. Moreover, this Android-based module obtained positive response from students proved by questionnaire result.